(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article highlights the factors that contribute to implementation of innovations in tourism sector of Uzbekistan. Moreover, it describes the organizational conditions necessary for a successful implementation of innovations in service sector. The author pays special attention to existing objects of innovation infrastructure while analyzing both advantages and disadvantages as the whole. Hence, research conducted on the ways of the implementation of innovations in the sphere of tourism and hospitality. The issue of enhancing interaction is also being considered tourism enterprises with development institutions innovation activities in the country, which act as a catalyst for private investments in priority sectors and industries economy and create conditions for the formation innovative infrastructure. The article addresses the issues of changing the personal training concept. Tourism industry needs the personal, which will be oriented towards innovation and quality growth. The author has developed a list organizational, informational and personnel activities and "Roadmap" for implementation innovation in tourism services and transition on the principles of the best available opportunities to reach tourism as one of the major sector of economy in the Republic of Uzbekistan.